Speciation of Candida using CHROMagar from Various clinical Specimens and their Antifungal Susceptibility Pattern at a Tertiary Care Hospital - Rajkumari, Sanjana; Adhikaree, Neetu (Journal of College of Medical Sciences-Nepal, 2020)
Background: Candida albicans remains the most common and are responsible for various clinical infections ranging from mucocutaneous infection to life threatening invasive diseases. But recent epidemiological data shift from C.albicans to non albicans Candida species and also increased resistance to antifungal drugs made the scenario a serious concern. Methods: A total of 156 Candida isolates from various clinical specimens received in the department of Microbiology were taken up for the study over a period of one year i.e. from March 2019 to February 2020. The Candida were grown on Sabouraud dextrose agar to be evaluated for colony appearance, macroscopic examination, Gram staining, germ tube, urea hydrolysis etc. The Candida isolates were speciated by using CHROMagar medium. Antifungal susceptibility testing was performed as recommended by Clinical and Laboratory Standards Institute (CLSI) M44-A document. Results: The isolation of non albicans Candida (54.5%) predominated over Candida albicans (45.5%). Non albicans Candida isolated were Candida tropcalis 40(25.6%), Candida krusei 21(13.4%), Candida glabrata 17(10.8%) and Candida dublinensis 07(4.4%) each. Candida species were all susceptible to Amphotericin B, followed by fluconazole (67.4%), miconazole (51.9%) and ketoconazole (22.5%). Conclusions: The accurate species identification of Candida is important for the treatment because not all species respond to the same treatment and also because of the increasing antifungal resistance. CHROMagar is a convenient and rapid method of identification of Candida species specially in resource limited poor settings. Keywords: antifungal susceptibility testing; Candida albicans; CHROMagar; non albicans Candida